2020
DOI: 10.1097/01.aoa.0000693736.15905.d4
|View full text |Cite
|
Sign up to set email alerts
|

Planned Early Delivery or Expectant Management for Late Preterm Preeclampsia (PHOENIX): A Randomized Controlled Trial

Abstract: (Lancet. 2019;394:1181–1190) Preeclampsia occurs in 2% to 3% of pregnant women and is associated with substantial maternal and neonatal morbidity and mortality. Prompt delivery is the recommended management for preeclamptic women after 37 weeks’ gestation, as this will decrease the risk of maternal complications while minimally affecting risk to the neonate at this gestational age. However, it is unclear what the best management strategy is for women who develop preeclampsia between 34 and 37 weeks’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 0 publications
1
33
0
1
Order By: Relevance
“…Thus, a large number of vasoactive cytokines enter the blood circulation to induce systemic inflammatory response and result in insufficient blood perfusion in all organs of the body. The placenta, as the most important target organ of severe preeclampsia, has an important influence on the outcomes of perinatal children with severe preeclampsia [17].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a large number of vasoactive cytokines enter the blood circulation to induce systemic inflammatory response and result in insufficient blood perfusion in all organs of the body. The placenta, as the most important target organ of severe preeclampsia, has an important influence on the outcomes of perinatal children with severe preeclampsia [17].…”
Section: Discussionmentioning
confidence: 99%
“…The capability of the screening model to additionally identify other placenta-associated complications and the consequently improved positive predictive value of the test may promote the acceptability and cost-effectiveness of uptake of daily low-dose aspirin for screen-positive women 52 . We recommend a comprehensive management policy for high-risk women, who could benefit, in terms of both maternal and neonatal health, not only from administration of low-dose aspirin, but also from closer monitoring, calcium supplementation 53,54 , appropriate gestational weight gain 55,56 , a healthy diet, timely diagnosis and, if necessary, transfer to another hospital 57 .…”
Section: Implications For Clinical Applicationmentioning
confidence: 99%
“…These rules are based on large randomized clinical trials conducted in recent years comparing induction of labor and expectant management. As is apparent from Table 1, iatrogenic delivery is not required for any of the common pregnancy conditions and appropriate monitoring is advised instead, perhaps with the exception of pre‐eclampsia, in which delivery between 34 and 37 weeks can be considered, 12,13 while for women with chronic hypertension the recommendation based on non‐randomized data is 38 weeks 14 . In pregnancies complicated by growth restriction at term, the DIGITAT study showed that the optimal timing of induction is around 38 weeks, 15 while in pregnancies with early‐onset growth restriction without fetal distress, earlier induction does not improve outcomes 16 .…”
Section: Clinical Scenarios and Issuesmentioning
confidence: 99%